2015
DOI: 10.1002/apj.1930
|View full text |Cite
|
Sign up to set email alerts
|

Fly ash supported Ni―Fe solid acid catalyst for efficient production of diesel additive: intensification through far‐infrared radiation

Abstract: Novel Ni-Fe solid acid catalyst was prepared through co-wet impregnation of Fe 2 (SO 4 ) 3 ·H 2 O and Ni (NO 3 ) 2 ·6H 2 O on fly ash (FA) support. XRD, BET-BJH, SEM-EDX, XPS and FTIR methods were employed to characterize the catalyst. The excellent catalyst activity was assessed and optimized in the production of methyl oleate (biodiesel/dieseladditive). The response surface methodology (RSM) computed optimal parametric values pertaining to maximum oleic acid (OA) conversion (98.37 ± 0.01%) were 15:1 methanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…11 It has been observed in this study that the efficacy of quartz halogen radiation (QHR; which represents near-infrared spectra) monolaurate synthesis was comparatively lower than the far infrared radiation. 11 It has been observed in this study that the efficacy of quartz halogen radiation (QHR; which represents near-infrared spectra) monolaurate synthesis was comparatively lower than the far infrared radiation.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…11 It has been observed in this study that the efficacy of quartz halogen radiation (QHR; which represents near-infrared spectra) monolaurate synthesis was comparatively lower than the far infrared radiation. 11 It has been observed in this study that the efficacy of quartz halogen radiation (QHR; which represents near-infrared spectra) monolaurate synthesis was comparatively lower than the far infrared radiation.…”
Section: Introductionmentioning
confidence: 67%
“…Although employment of A15 has been effective in esterification, nevertheless, energy-intensive reaction conditions could be overcome by the application of energy-efficient electromagnetic radiation as revealed through high glyceryl monolaurate yield (80.2%) only in 30 min and at 353 K in a batch reactor under the influence of infrared radiation. 11 It has been observed in this study that the efficacy of quartz halogen radiation (QHR; which represents near-infrared spectra) monolaurate synthesis was comparatively lower than the far infrared radiation. This could have been further improved through the employment of photosensitive catalyst, for example, TiO 2 , as A15 has no photocatalytic property.…”
Section: Introductionmentioning
confidence: 67%
“…Therefore, the improvement in ODA conversion and MOG selectivity upon application of electromagnetic energy can be explained by the fact that FIR could infiltrate into the reaction mixture and can transmit immense energy, 31 thus rendering intense molecular collision (due to stretching and bending vibrations) and excitation that promotes faster reactions. 32,33 Whereas ultrasonic energy results in intense turbulence, acoustic streaming and thus can remove the phase boundaries by rapid compression and rarefaction of the Gl/ODA reaction medium, 34 hence overcoming the effect of diffusional hindrance. Therefore, it could be concluded that the coupled effect of ultrasonic (US) and FIR energies can immensely accelerate the Gl/ODA esterification, thereby reaching max-imum conversion within a much shorter time compared to IRWPBR and TBR, respectively.…”
Section: Performances Of Different Reactorsmentioning
confidence: 99%